Kendala Kerjasama Informasi dan Jaringan di Perpustakaan - Surya Ningsih Wijaya Sitompu; Dina Mei Saridina; Fikri Aprialdi; Ahmad Tuah Wijaya; Yusniah Yusniah (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
The library's ability to grow is constrained by the times. The internet is progressively taking the place of libraries as a source of knowledge, starting with a poor mainset community and moving on to the library, internal ill-preparedness, and even paired with its presence. Based on these factors, this study aims to give a general overview of how the library can overcome internal issues by implementing internal knowledge management solutions as a catalyst for development, with notabene serving as the primary force behind the library's readiness to take on the challenge. The technique employed in this analysis of literature from several scientific sources include books and journal articles both in print and online. The findings of this study demonstrated that knowledge management can be used as a solution because it is essentially knowledge management applied to overcome unpreparedness or internal problems. By capturing knowledge stored by employees, knowledge management serves as a tool for both internal and external improvements, acting as a spark for ideas on problems faced. The first step in knowledge management to remove barriers from the library is to find people who share your perspective and give librarians opportunity and visibility to participate in managerial operations. The second is the procedure for managing activities like the creation of a community of practice for knowledge sharing and training. However, it must include specific actions like scheduling, discussion points, and the product that will be produced. The technology to create a knowledge management portal, which can only be accessible internally through the intranet, is the third item on the list. In order to reduce the likelihood that libraries would be unprepared to handle the difficulties of the information age, it is suggested that the library follow the following outcomes as routinely as feasible. Keyword: librarys problems, librarians, knowledge management, knowledge sharing